Male Breast Cancer Initially Misdiagnosed as Gynecomastia: A Case Report of Delayed Diagnosis in a 62-Year-Old Man - Alendra Chakramurty; Tresnawaty Tresnawaty (CV. Publikasi Indonesia, 2026)
Male breast cancer is a rare malignancy, accounting for approximately 1% of all breast cancer cases; however, its rarity frequently contributes to delayed diagnosis. Gynecomastia, a benign proliferation of male breast glandular tissue, may mimic early-stage male breast cancer and represents a significant diagnostic challenge. This case report describes a 62-year-old man with a right subareolar breast mass that was initially diagnosed as gynecomastia based solely on clinical assessment. Conservative management was pursued until progressive enlargement and nipple retraction prompted surgical referral. Core needle biopsy confirmed invasive ductal carcinoma, not otherwise specified (NOS), Grade II, with pathological staging of pT2N1M0 (Stage IIB). The patient underwent modified radical mastectomy followed by adjuvant chemotherapy and hormonal therapy. This case highlights that male breast cancer predominantly presents as invasive ductal carcinoma (85–95%), with hormone receptor positivity observed in more than 90% of cases. Clinical red flags can help distinguish male breast cancer from gynecomastia when systematically assessed, while core needle biopsy remains the diagnostic standard. This case underscores the critical importance of tissue biopsy in male patients presenting with a unilateral, firm, or eccentric breast mass, regardless of initial clinical suspicion. Early histopathological evaluation is essential to minimize diagnostic errors and optimize patient outcomes.